THEORETICAL STUDY OF THE PRINCIPLES OF MODERN BACTERIOPHAGIC THERAPY - Yerkhova, Anna; Katynska, Maryna (The Ukrainian Scientific Medical Youth Journal, 2021)
Phagotherapy is an approach to treating bacterial infections using bacteriophages. Bacteria viruses can be used as an alternative to antibiotics in the widespread development of antibiotic resistance among microbial strains. This problem becomes more and more over time because of the misuse of antibiotic therapy. In the nature of bacteriophages have already laid specificity for certain microbes, while they do not harm the human body. Treatment using bacterium viruses provides an alternative to traditional methods in bacterial infections. It remains possible to develop bacterial resistance to bacteriophages, but such resistance is easier to overcome than antibiotic resistance. Because bacteriophages can evolve, like bacteria, causing resistance to disappear. Bacteriophages are specific and exhibit their effect on one or more species, (Maghsoodi, Chatterjee, Andricioaei, ＆ Perkins, 2019) while traditional antibiotic therapy affects both harmful bacteria and the rest of the human body microflora. It is the peculiarity of bacteriophages to exhibit their therapeutic effect on a limited range of microbes make them safe for beneficial bacteria (Choudhury, Tanmoy, Maiti, Biswajit, Venugopal, Karunasagar, ＆Indrani, 2019). Also, a significant advantage is that lytic viruses of bacteria, unlike antibiotics, do not cause bacteriostat, but have only a bactericidal effect, which prevents a possible relapse of the infectious process for a longer period. Some scientists suggest the theory that administering one dose of bacteriophages is enough to cope with the causative agent of the disease, but the main criterion is the immune clearance of phages. Also, a significant advantage in favor of using of bacteriophage drugs is those bacteriophages are distributed throughout the globe, in addition, their composition and species diversity are huge. From this point there is one minus - in our time, the mechanism of patenting phages remains incomprehensible. For pharmaceutical companies, there are many questions about the biodiversity sharing, as it is necessary to amend various protocols. However, despite this, bacteriophages bred in the laboratory attract the attention of scientists in the field of intellectual property(Saha,&Mukherjee, 2019). The article contains a classification of bacteriophages, a description of the mechanism of action on bacteria and their recognition, a comparison of bacterium viruses with antibiotics. The purpose of this study was to describe the modern classification of bacteriophages, to substantiate the use of cellular phages, and to describe the principles of bacteriophages treatment of diseases associated with the respiratory system.